Females have a larger hippocampus than males in the brood-parasitic brown-headed cowbird. - Sherry, D F (1993)
Females of the brood-parasitic brown-headed cowbird (Molothrus ater) search for host nests in which to lay their eggs. Females normally return to lay a single egg from one to several days after first locating a potential host nest and lay up to 40 eggs in a breeding season. Male brown-headed cowbirds do not assist females in locating nests. We predicted that the spatial abilities required to locate and return accurately to host nests may have produced a sex difference in the size of the hippocampal complex in cowbirds, in favor of females. The size of the hippocampal complex, relative to size of the telencephalon, was found to be greater in female than in male cowbirds. No sex difference was found in two closely related nonparasitic icterines, the red-winged blackbird (Agelaius phoeniceus) and the common grackle (Quiscalus quiscula). Other differences among these species in parental care, migration, foraging, and diet are unlikely to have produced the sex difference attributed to search for host nests by female cowbirds. This is one of few indications, in any species, of greater specialization for spatial ability in females and confirms that use of space, rather than sex, breeding system, or foraging behavior per se, can influence the relative size of the hippocampus.